Control of ColE1 DNA replication: the rop gene product negatively affects transcription from the replication primer promoter. - Cesareni, G (1982)
A 600-base-pair region essential for ColE1 and pMBl plasmid replication contains two promoters responsible for the synthesis of two RNA molecules central to copy number control. One promoter directs synthesis of the primer RNA precursor. The second promoter directs the synthesis of a small RNA molecule, RNAl, which acts in trans to inhibit processing of the RNA primer precursor. We have fused each promoter to the beta-galactosidase structural gene contained in a lambda phage. Expression of the RNAl promoter in lysogens is not influenced by the presence of wild-type pMBl or ColEl plasmids residing in the cell. Transcription from the RNA primer promoter, however, is repressed by the product of a trans-acting plasmid gene product, which we have designated rop (for repressor of primer). The rop gene maps downstream from the replication origin in a region that encodes a polypeptide of 63 amino acids whose sequence is completely conserved in pMBl and ColE1. We propose that this polypeptide is the rop gene product and that it regulates plasmid DNA replication by modulating the initiation of transcription of the primer RNA precursor.